Pharmacokinetics of olverembatinib (HQP1351) in the presence of a strong CYP3A4 inhibitor (itraconazole) or inducer (rifampin) in healthy volunteers - Hengbang Wang; Yun Yang; Zi Chen; Lei Fu; Min Yu; Lixin Jiang; Cunlin Wang; Lichuang Men; Ilisse Minto; Dajun Yang; Yifan Zhai (Wiley, 2024)
Abstract Olverembatinib (HQP1351) is a BCR‐ABL1 tyrosine kinase inhibitor with promising clinical activity. It is approved in China for the treatment of patients with chronic myeloid leukemia harboring drug‐resistant mutations, such as T315I. In vitro studies suggested that metabolism of olverembatinib is primarily mediated by cytochrome P450 (CYP3A4). The effects of CYP3A4 inhibition and induction on the pharmacokinetics of olverembatinib were evaluated in an open‐label, 2‐part, fixed‐sequence study in healthy volunteers. In Part 1 of this study, 16 participants received a single oral dose of olverembatinib (20 mg) and the oral CYP3A4 inhibitor itraconazole (200 mg). In Part 2, 16 participants received a single oral dose of olverembatinib (40 mg) and the oral CYP3A4 inducer rifampin (600 mg). To measure pharmacokinetic parameters, serial blood samples were collected after administration of olverembatinib alone and combined with itraconazole or rifampin. Coadministration of olverembatinib with itraconazole increased the peak plasma concentration of olverembatinib, its area under the time‐concentration curve (AUC)0‐last, and AUC0‐inf by 75.63%, 147.06%, and 158.66%, respectively. Coadministration with rifampin decreased these same variables by 61.27%, 74.21%, and 75.19%, respectively. These results confirm that olverembatinib is primarily metabolized by CYP3A4 in humans, suggesting that caution should be exercised with concurrent use of olverembatinib and strong CYP3A4 inhibitors or inducers.